ENGLISH LEARNING MEDIA BASED ON LOCAL WISDOM FOR TEACHING WRITING DESCRIPTIVE TEXT - Yokie Prasetya Dharma; Thomas Joni Verawanto Aristo; Sijono Sijono; Henry Elisa (STKIP Persada Khatulistiwa Sintang, 2021)
One of the learning models offered to overcome writing difficulties is a learning media based on local wisdom. Local wisdom is basic knowledge obtained from everyday life. This model will make students interested and like writing activities because it was close to their daily life. Social function or communicative approach of descriptive text is to describe a particular person, place, or thing in detail or clearly. This research was conducted through Classroom Action Research. Classroom Action research is about working towards practical outcomes, and also about creating new forms of understanding. In this research, learning media based on local wisdom has a good impact on improving students' ability to write descriptive texts, including that students can understand several local cultures that are close to their lives so that they can preserve the culture more broadly. This English learning media based on local wisdom can be the effective technique and it could be used as the alternative way in teaching writing because the technique was easy to be implemented and it was the one of interesting technique which very closed to the students’ learning activities